Social Science Education in Indian Schools: Review of Research and Public Discourse - Srinivasan, M.V. (INDIAN EDUCATIONAL REVIEW, 2019)
School social science curriculum includes the study of history, geography, economics, political science and sociology. This review attempts to bring together the review of research as well as the major debates that took place in the curricular history of school social sciences during 2000–2015. Social science education is in a paradoxical situation today. People, media and the government find teaching social sciences in schools as very important. But only a small section of the society gives importance to study social science as a curricular choice. Social science curriculum development process is now well documented. In the past, researchers examined social science and curricular materials only from structural aspects. Today, many social science concepts and tools, advanced research methods have begun to be applied to explore Indian school social science classrooms. This period has witnessed serious public discourse on school social science. Both social and educational philosophical battles drove social science curriculum formulation. Model children-friendly social science curricular materials and information communication technologies are available for learners but social science teachers are not yet ready. This is due to prevalence of wide gap between the expectations of curricular policies and the capacity, and acceptance level of social science teachers. Today, the civil society organisations and media are vigilant with regard to what goes into social science textbooks. This is a welcome development.